2019
DOI: 10.1370/afm.2385
|View full text |Cite
|
Sign up to set email alerts
|

Following Uninsured Patients Through Medicaid Expansion: Ambulatory Care Use and Diagnosed Conditions

Abstract: PURPOSE The Patient Protection and Affordable Care Act (ACA) has improved access to health insurance, yet millions remain uninsured. Many patients who remain uninsured access care at community health centers (CHCs); however, little is known about their health conditions and health care use. We assessed ambulatory care use and diagnosed health conditions among a cohort of CHC patients uninsured before enactment of the ACA (pre-ACA: January 1, 2012 to December 31, 2013) and followed them after enactment (post-AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Medicaid expansion under the ACA decreased the number of uninsured individuals in the low-income population, and there have been several other population health benefits, including improving access to care, use patterns, and self-reported health outcomes. 6,[28][29][30] The current study results suggested that Medicaid expansion also may have improved outcomes in patients with screening-amenable cancers. In the population of low-income, potentially Medicaid-eligible adults in Ohio (a state that was part of the first round of expansions in 2014), the odds of being diagnosed with metastatic breast, cervical, colorectal, or lung cancers decreased in the postexpansion period.…”
Section: Discussionmentioning
confidence: 97%
“…Medicaid expansion under the ACA decreased the number of uninsured individuals in the low-income population, and there have been several other population health benefits, including improving access to care, use patterns, and self-reported health outcomes. 6,[28][29][30] The current study results suggested that Medicaid expansion also may have improved outcomes in patients with screening-amenable cancers. In the population of low-income, potentially Medicaid-eligible adults in Ohio (a state that was part of the first round of expansions in 2014), the odds of being diagnosed with metastatic breast, cervical, colorectal, or lung cancers decreased in the postexpansion period.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study in the OCHIN network found that those who remained uninsured following the Affordable Care Act expansion were more likely to be Hispanic, which had among the lowest rates of benzodiazepine co-prescribing throughout most the study period. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The overall similarity in attitudes is notable, given differences in generational attitudes, and may reflect a commonality of concerns among individuals with an interest in healthcare [ 50 ]. The greater emphasis on problems related to the uninsured in our study may related to increased public awareness of the issue [ 51 ].…”
Section: Discussionmentioning
confidence: 99%